Implementation and Utilization of Family Latrines in Allu Hamlet, Minasa Baji Village, Bantimurung Sub-district, Maros Regency - Suminar, Saka; Bare Telan, Albina; M Dukabain, Olga; Suluh, Debora G; Vanchapo, Antonius Rino; Agustina, Agustina; Aulia Rahmat, Rezqiqah (International Journal of Health Sciences, 2023)
Based on data obtained from local agencies, it was recorded that there were 155 family heads in Allu Hamlet, Minasa Baji Village, Bantimurung District, Maros Regency, but only 60% of family heads had family latrines that met the requirements or health standards, thus there were still 40% of family heads who did not have family latrines that met the requirements, this could be a big problem if not immediately addressed, because it could be the cause of environmental pollution which in turn could cause various diseases. The purpose of the study was to determine the utilization of family latrines in Allu Hamlet, Minasabaji Village, Bantimurung District, Maros Regency. This type of research is "Descriptive" research to determine the utilization of family latrines. Then the following conclusions can be drawn: 1). Respondents with less knowledge have a greater chance of not utilizing a qualified family latrine, namely out of 33 respondents with less knowledge there are 27 who do not utilize a qualified family latrine. 2). Respondents with poor attitudes have a greater chance of not utilizing qualified family latrines, namely out of 37 respondents with poor attitudes there are 25 who do not utilize qualified family latrines. 3). Respondents with less income have a greater chance of not utilizing eligible family latrines, namely out of 26 respondents with less income there are 17 who do not use eligible family latrines.